2023
DOI: 10.1057/s41599-023-01625-x
|View full text |Cite
|
Sign up to set email alerts
|

The perception of plastic surgery during the COVID-19 pandemic—an analysis of online search patterns on a medical information platform

Abstract: In 2020, the COVID-19 pandemic impacted global life and transitioned economies and societal perceptions of life as we knew it. Professional and social life mostly ground to a nadir during the first lockdown in Europe in March. As a consequence, measures aimed at preventing the spread of the virus were established in medical facilities also and elective plastic surgery procedures were temporarily suspended in our clinic and others. A majority of the population, including those potentially contemplating plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Survey studies have shown evidence that many of the factors driving the trend for plastic surgery procedures, both surgical and nonsurgical, include a renewed focus on self-image after the pandemic, more instances of online video calling, and a desire to improve their quality of life after the pandemic 39–41 . Online search trends similarly reflect this increased interest in plastic surgery, showing evidence that since 2020, there has been a rise in searches for various aesthetic procedures 42–44 . What the analysis in this study suggests is that there may be new factors to consider when a patient is deciding to undergo plastic surgery that may have been precipitated, instead of temporarily halted, by a worldwide viral pandemic.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Survey studies have shown evidence that many of the factors driving the trend for plastic surgery procedures, both surgical and nonsurgical, include a renewed focus on self-image after the pandemic, more instances of online video calling, and a desire to improve their quality of life after the pandemic 39–41 . Online search trends similarly reflect this increased interest in plastic surgery, showing evidence that since 2020, there has been a rise in searches for various aesthetic procedures 42–44 . What the analysis in this study suggests is that there may be new factors to consider when a patient is deciding to undergo plastic surgery that may have been precipitated, instead of temporarily halted, by a worldwide viral pandemic.…”
Section: Discussionmentioning
confidence: 63%
“…However, the lack of statistically significant decline in this study in the initial months of the pandemic does not explain the surge in reduction mammaplasty cases in the 2 years after the pandemic. Evidence in the literature shows that, after the first year of the pandemic, there has been increased interest and demand for plastic surgery procedures driven by factors surrounding the new norm of the pandemic 39,42–44 . These findings provide additional evidence for factors potentially contributing to patients pursuing reduction mammoplasty post-COVID including convenience resulting from time off due to pandemic, meeting insurance-covered reduction criteria, and projected recovery time.…”
Section: Discussionmentioning
confidence: 94%